2019
DOI: 10.5217/ir.2018.00173
|View full text |Cite
|
Sign up to set email alerts
|

Real-time data monitoring for ulcerative colitis: patient perception and qualitative analysis

Abstract: Background/Aims TrueColours ulcerative colitis (TCUC) is a comprehensive web-based program that functions through email, providing direct links to questionnaires. Several similar programs are available, however patient perspectives are unexplored. Methods A pilot study was conducted to determine feasibility, usability and patient perceptions of real-time data collection (daily symptoms, fortnightly quality of life, 3 monthly outcomes). TCUC was adapted from a web-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…109 Daily monitoring of UC through TrueColours UC improved UC management while also reducing the burden placed on individual and healthcare services. 110 These applications can not only remotely monitor patients via electronic patient-reported outcome measures (PROs) or device-generated data (such as activity trackers) but also improves patient engagement. 111 The goal of recent IBD therapies is moving toward a therapeutic-targeted strategy using PROs, biomarkers of inflammation, and mucosal healing to optimize therapeutics and should also be used for the treatment of EIMs.…”
Section: Key Recommendations For Improving the Disease Course And Primentioning
confidence: 99%
See 1 more Smart Citation
“…109 Daily monitoring of UC through TrueColours UC improved UC management while also reducing the burden placed on individual and healthcare services. 110 These applications can not only remotely monitor patients via electronic patient-reported outcome measures (PROs) or device-generated data (such as activity trackers) but also improves patient engagement. 111 The goal of recent IBD therapies is moving toward a therapeutic-targeted strategy using PROs, biomarkers of inflammation, and mucosal healing to optimize therapeutics and should also be used for the treatment of EIMs.…”
Section: Key Recommendations For Improving the Disease Course And Primentioning
confidence: 99%
“…The role of mobile applicable for the self-management of IBD by patients will continue to increase by providing a more efficient, effective, and good quality healthcare system at lower costs [ 109 ]. Daily monitoring of UC through TrueColours UC improved UC management while also reducing the burden placed on individual and healthcare services [ 110 ]. These applications can not only remotely monitor patients via electronic patient-reported outcome measures (PROs) or device-generated data (such as activity trackers) but also improves patient engagement [ 111 ].…”
Section: Key Recommendations For Improving the Disease Course And Primentioning
confidence: 99%
“…The quantitative studies examined the effectiveness of the following interventions: web‐guided intervention, IBD management through an electronic health record patient portal, home tele‐management, telemedicine, short message services (SMS) for remote monitoring, tele‐monitoring using a mobile application, monitoring of fecal calprotectin (an inflammatory biomarker) using a smartphone application, nurse‐led annual telephone monitoring, a secure web‐based program for medication monitoring, videoconference clinics, a decision support tool to customize self‐management, a web‐based application for monitoring disease activity, and telemedicine virtual visits. The second qualitative study (Walsh et al, 2019) also evaluated a web‐based program that remotely assessed patient‐reported outcomes. The qualitative studies used a semi‐structured questionnaire to collect data through face‐to‐face interviews (Walsh et al, 2019) and telephone interviews (Reich et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The second qualitative study (Walsh et al, 2019) also evaluated a web‐based program that remotely assessed patient‐reported outcomes. The qualitative studies used a semi‐structured questionnaire to collect data through face‐to‐face interviews (Walsh et al, 2019) and telephone interviews (Reich et al, 2019). Both studies employed thematic analysis for the data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation